Novel Compound Heterozygous Variants in MKS1 Leading to Joubert Syndrome - Luo, Minna; He, Ruida; Lin, Zaisheng; Shen, Yue; Zhang, Guangyu; Cao, Zongfu; Lu, Chao; Meng, Dan; Zhang, Jing; Ma, Xu; Cao, Muqing (Frontiers in Genetics, 2020)
Joubert syndrome (JBTS) and Meckel-Gruber syndrome (MKS) are rare recessive disorders caused by defects of cilia, and they share overlapping clinical features and allelic loci. Mutations of MKS1 contribute approximately 7% to all MKS cases and are found in some JBTS patients. Here, we describe a JBTS patient with two novel mutations of MKS1. Whole exome sequencing revealed c.191-1G>A and c.1058delG compound heterozygous variants. The patient presented with typical cerebellar vermis hypoplasia, hypotonia, and developmental delay, but without other renal/hepatic involvement or polydactyly. Functional studies showed that the c.1058delG mutation disrupts the B9 domain of MKS1, attenuates the interactions with B9D2, and impairs its ciliary localization at the transition zone (TZ), indicating that the B9 domain of MKS1 is essential for the integrity of the B9 protein complex and localization of MKS1 at the TZ. This work expands the mutation spectrum of MKS1 and elucidates the clinical heterogeneity of MKS1-related ciliopathies.